Pemberian Iradiasi Sinar Gamma dalam Meningkatkan Pertumbuhan dan Produksi Tanaman Cabai Merah (Capsicum annuum L.) - Evi Julianita Harahap; Marziah (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2025)
The research used a non-factorial randomized block design consisting of 8 levels with 3 replications. The treatment factors studied were red chili seeds that had been given gamma irradiation, namely as follows: G0 = Control, G1 = 50 Gray, G2 = 100 Gray, G3 = 150 Gray, G4 = 200 Gray, G5 = 250 Gray, G6 = 300 Gray, and G7 = 350 Gray. If based on the F test results the research results show a significant difference, then it will be continued with further tests, namely the least significant difference test (BNT) at the 5% level. The chili seeds used are the Lotanbar chili variety. The results showed that the dose of gamma irradiation had a significant difference in the diameter of the stem base, plant height, fruit weight per red chili plant, and number of fruit per plant. Giving a gamma ray irradiation dose of 150 Gray (G3) increases the vegetative growth of red chili plants, namely plant height and stem base diameter. Providing a gamma ray irradiation dose of 200 Gray (G4) increases the generative growth of red chili plants, namely the number of fruit per plant and the weight of fruit per plant.